The Microstratigraphy of Two Peat Sequences from Northeastern Newfounland - Davis, A.; Wickham, S. (Géographie physique et Quaternaire, 1987)
ABSTRACTCommonly, the ombrotrophic peats of Newfoundland have a well-defined banded appearance. Each band consists of a light-coloured lower section and a dark upper component. The bands are separated by abrupt recurrence surfaces. The regularity of the bands implies cyclicity. The physical, elemental, micro- and macro-stratigraphies of two banded profiles from the Wesleyville area were examined in an attempt to document the differences and to provide insight into cause. Ash content, fibre content, bulk density, water content and water retention were measured. The latter three showed consistent changes through each profile. There were no obvious patterns in the values for the biologically active elements that were measured (Mg, Cl, Ca, Na, Al, Mn and I), but the curves for Br, V, and U, biologically inert elements, showed systematic variations that appear to reflect variations in peat accumulation rate. The pollen, spore and macrofossil stratigraphies were generally complacent, although the representation of Sphagnum macrofossils and spores varied regularly as did pollen and spore concentrations. Each light-dark sequence appears to reflect a cycle of self-sustaining hydrologie changes involving changes in community composition, and in oxidation and accumulation rate, rather than climate. The cycles appear to be ca. 700 years in length, and are system-wide, but with variable lag times.